STRES AKADEMIK DAN KEMANDIRIAN BELAJAR TERHADAP ACADEMIC FLOW PADA MAHASISWA S1 - Prameswari, Radika; Purwantini, Lucky; Hanoum, Magdalena (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2025)
Understanding the dynamics that influence student engagement and academic performance amidst increasingly complex academic challenges and pressures is crucial. The aim of this study is to describe and analyze the relationships between variables and to examine the impact of academic stress and self- regulated learning on academic flow. This research employs a quantitative approach with a sample of 366 students, selected using stratified random sampling. Data collection methods include interviews and psychological scales, specifically the academic stress scale, the self-regulated learning scale, and the academic flow scale. Reliability testing was conducted using Cronbach's alpha, and data analysis involved descriptive analysis, normality tests, and linearity tests. The results indicate a negative relationship between academic stress and academic flow (r = -0.145, p = 0.005) and a positive relationship between self-regulated learning and academic flow (r = 0.654, p = 0.000). Academic stress accounts for 1.7% of the variance in academic flow, while self-regulated learning accounts for 43%, with the remaining 55.3% influenced by other variables.